2013
DOI: 10.2319/011112-23.1
|View full text |Cite
|
Sign up to set email alerts
|

Tooth sizes in nonsyndromic hypodontia patients

Abstract: Objective: To evaluate and compare the sizes of teeth in mild and severe hypodontia patients with those of healthy controls. Materials and Methods: Dental casts of 154 patients with two or more congenitally missing teeth were obtained. Patients were divided into two groups according to severity of hypodontia. Group I (mild) consisted of 118 patients with two to five missing teeth. Group II (severe) consisted of 36 patients with six or more missing teeth. In addition, a control group was included, which consist… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
17
4

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(31 citation statements)
references
References 29 publications
6
17
4
Order By: Relevance
“…Subjects with systemic diseases affect the growth and development of the teeth and tooth agenesis excluded from the study because dental anomalies like hypodontia could affect tooth development and eruption. [22,23] In addition, malocclusions such as cross bite and sagittal skeletal discrepancies might affect the dental development as reported by some authors. [24,25] In the present study, care was taken while selecting the patients so that none had posterior cross bite and skeletal sagittal malocclusions.…”
Section: Discussionmentioning
confidence: 99%
“…Subjects with systemic diseases affect the growth and development of the teeth and tooth agenesis excluded from the study because dental anomalies like hypodontia could affect tooth development and eruption. [22,23] In addition, malocclusions such as cross bite and sagittal skeletal discrepancies might affect the dental development as reported by some authors. [24,25] In the present study, care was taken while selecting the patients so that none had posterior cross bite and skeletal sagittal malocclusions.…”
Section: Discussionmentioning
confidence: 99%
“…[ 2 3 4 8 14 20 31 32 33 ] While some researchers have reported that the size of teeth and the width of the dental arch are not related to dental agenesis,[ 68 ] some others reported conflicting results indicating that CMT is associated with dental anomalies such as microdontia and decreases in the size of the incisors and canines as well as conical or tapered teeth such as peg lateral. [ 14 28 31 164 165 ] However, some investigators did not find a link between tooth agenesis and microdontia but with peg laterals. [ 14 ] They concluded that CMT was not associated with changes in the overall tooth size, while changes in tooth morphology especially in the maxillary lateral incisors might still be possible.…”
Section: The Association Of Cmt With Other Dental Anomaliesmentioning
confidence: 99%
“…Both CMT and taurodontism seem to be a part of syndromes characterized by decreased mitotic cellular activity which might also affect dental germ development. [ 4 ] On the other hand, some other studies found clear associations between both mild and severe CMT and reduced tooth size,[ 21 32 160 165 167 ] especially in the upper laterals (in the mesiodistal dimension) and the lower canines (the labiolingual dimension). [ 165 ] The latter agrees with the synergism and allelism of major genes possibly affecting CMT.…”
Section: The Association Of Cmt With Other Dental Anomaliesmentioning
confidence: 99%
“…McKeown et al [ 15 ] found a reduction in crown width in both buccolingual and mesiodistal dimensions in cases with oligodontia. Gungor and Turkkahraman [ 16 ] evaluated tooth dimensions in mild and severe hypodontia cases and found that the mesiodistal and buccolingual dimensions of the teeth in both mild and severe hypodontia were smaller. In addition, the maxillary lateral incisor showed the greatest reduction in the mesiodistal dimension.…”
Section: Discussionmentioning
confidence: 99%